Heterogeneous effects of monetary and non-monetary job characteristics on job attractiveness in nursing - Martin Kroczek; Philipp Kugler (Institut für Angewandte Wirtschaftsforschung (IAW), 2022)
We apply a novel methodological approach described by Chernozhukov, Fern'andez-Val & Luo (2018), to analyze preference heterogeneity regarding non-monetary job characteristics and trade-offs between wage and non-monetary job characteristics. Using this approach, we can describe preference heterogeneity more concise than with subgroup analysis. Analyzing data from a selfconducted factorial survey experiment on nurses, we find significant effect heterogeneity regarding the single job characteristics and the trade-offs between wage and non-monetary job characteristics. We also find positive interaction effects between wage and other job characteristics. We further analyze which factors are associated with effect heterogeneity. Working hours and gender appear to be the main drivers of these effects. We also find differences regarding the sources of a nurse's motivation to initially choose the nursing occupation. Differentiation of job characteristics (job offers) to fit different preferences can therefore be a more effective and efficient way to attract workers than a "one size fits all" solution. Regarding nursing jobs, there is some evidence for such differentiation.
Keywords: J22; J31; J32; I11; 330; labor supply; wage; non-monetary job characteristics; heterogeneity analysis; nurses